ANALISIS FRAMING PEMBERITAAN PESAN DIBALIK PEMBAGIAN MOTOR DINAS OLEH BUPATI KLATEN DI SOLOPOS.COM - Sari, Indita Novita (Solidaritas: Jurnal Ilmu-Ilmu Sosial, 2020)
Online media is required to convey the latest information to the community. The red motorcycle division policy is one of the policies that must be communicated to the public. Solopos.com as an online media that continues to highlight the policy aims to convey information according to the objectivies of policy conducted by regent Klaten, Sri Mulyani. This research aims to analyze the viewpoint of solopos.com in framing the message of the distribution of motorcycles in the service by regent Klaten. So from the analyze can be know point of view of journalists Solopos.com in delivering the news. Framing analyze is done with Zhongdang Pan and Kosicki models with a qualitative approach. The object in this study is news related to the message behind the division of motorcycling service by regent Klaten which was loaded in Solopos.com from 23 november to 28 november 2019. The results showed that framing done by Solopos.com was a critique of Klaten regent as a regent who capitalized on his post to conduct his preterm campaign by utilizing state facilities by making the motorcycle division policy for village head, village secretary and sexy order and security in Klaten. From the policy there were political message of the regent campaign to seek support from the beneficiaries of the policy. Kata Kunci : Analisis Framing, Berita Kritik, Bupati Klaten, Solopos.com.